Gestión administrativa-financiera y su incidencia en el cumplimiento presupuestario del gobierno autónomo descentralizado municipal del cantón Quinsaloma, período 2013-2014, Plan administrativo. - Lara LLanos, Liandri Alvarado (2016)
This thesis Administrative Management - Financial and its impact on the financialperformance of Decentralized Autonomous Municipal Government of the CantonQuinsaloma, 2013-2014. Business plan, was conducted in order to know thereality of it, and in this way help municipal authorities to make wise decisions onbehalf of the county. For the development of this thesis the following objectives;analyzing the administrative and financial management of GAD Canton MunicipalQuinsaloma, establish management indicators using the financial resources of theinstitution, determine budget compliance in the execution of works planned by thecanton GADM Quinsaloma and design an administrative plan 2015-2019 toimprove compliance with the GAD budget Canton Municipal Quinsaloma. This research was conducted using the following methods; inductive, deductive,analytical and observation, instructional research used were interview the Mayor,Deputy Mayor and Chief Financial Officer of the Autonomous GovernmentDecentralized Quinsaloma were made, and surveys were applied to workers financial administrative area and Canton Quinsaloma inhabitants. The results ofthis study revealed the following: the inhabitants of the canton Quinsaloma andemployees of GAD Municipal consider the administrative and financialmanagement of the institution is not entirely satisfactory, according to the resultsof the indicators, it was possible to know that the handling of technological goods,equipment, machinery and tools GAD Municipal Canton Quinsaloma is efficient ina 84.64%, with a gap of 15.36%, while the internal compliance procedures areeffective in 71%, in terms of ethics with which it is carried out the budget plan is90, 10% and the economy of financial resources proved reliable in 77.66%, thelevel of budgetary compliance is 80% which is considered high by the CFO, whichshows that there is a deficiency of 20%, planning the budget is done based on theneeds of the population and income of the Municipality.